Neutronic Design for Heat Pipe Reactor With Annular and Accident Tolerant Fuels - Cai, Boshuai; Chen, Shengli; Wu, Tianfan; Wang, Yujing; Zhang, Zhaozhan; Yuan, Cenxi; Zhang, Chunyu; Ge, Yulin (Frontiers in Energy Research, 2021)
Several core designs of heat pipe reactors with megawatt power were proposed for extreme environments, such as the deep space and the deep sea. In the present work, a heat pipe design is proposed with an annular fuel rod to replace the cylindrical and hexagon fuel rods. In addition, accident tolerant fuels, such as the UN and U3Si2 fuels, are considered to be implemented. The neutronic properties, including lifetime, criticality, and axial power distribution, are systematically investigated for the new reactor design.